Evaluating of the Synergistic Effect of three Essential Oils on the Virulence Factors (resistance gene) of Pseudomonas aeruginosa and Serratia fonticola Isolated from Wounds - Muhammad, Sadiq R.; Abed, Ibrahim J. (Iraqi Journal of Science, 2023)
Depending on the high resistance to antibiotics, five isolates of Pseudomonas aeruginosa and 7 isolates of Serratia fonticola were selected out of 150 bacterial isolates from burn wards in Baghdad hospitals, which were later identified by VITEK2. A susceptibility test was done by using 15 antibiotics. The results showed that all the selected isolates were resistant to antibiotics: AMP, CTX, CAZ, GEN, PIP, TIC and TMP especially, while they were sensitive to IPE. The essential oils of Aloysia citrodora (Family: Verbenaceae), Rosmarinus officinalis (Family: Lamiaceae) and Thymus vulgaris (Family: Lamiaceae) were extracted by the Clevenger. The synergistic effect of essential oils of these plants on bacterial growth were studied by determining the MIC of essential oils for P. aeruginosa and S. fonticola. The MIC concentration of P. aeruginosa was: 2500 ppm of A. citrodora, 2500 ppm of R. officinalis, 2500 ppm of T. vulgaris, whilst the synergistic effect of each two plants was:1250 ppm of A. citrodora with 2500 ppm of R. officinalis, 1250 ppm of A. citrodora with 312.5 ppm of T. vulgaris, 1250 ppm of R. officinalis with 156.25 ppm of T. vulgaris, whereas the synergistic effect of three plants was: 156.25 ppm of A. citrodora with 156.25 ppm of R. officinalis and 39.0625 ppm T. vulgaris. While the MIC concentration of S. fonticola was: 1250 ppm of A. citrodora, 5000 ppm of R. officinalis, 1250 ppm of T. vulgaris, whilst the synergistic effect of each two plants was: 1250 ppm of A. citrodora with 2500 ppm of R. officinalis, 1250 ppm of A. citrodora with 312.5 ppm of T. vulgaris, 1250 ppm of R. officinalis with 156.25 ppm of T. vulgaris, whereas the synergistic effect of three plants was: 312.5 ppm of A. citrodora with 312.5 ppm of R. officinalis and 78.125 ppm T. vulgaris. The results of bacterial gene expression showed that three isolates of P. aeruginosa had a mexB gene expression that ranged between 2.5 - 0.4 (concentration 1) and 2.8 to 0.6 (concentration 2). It increased in two isolates and decreased in one isolate. The melting point ranged between 90.91 - 91.280C compared with 89.89 to 90.330C for fbp gene. Whereas S. fonticola did not have blaKPc gene, instead it had blaTEM gene with the gene expression ranging between 2.4 - 0.1 (concentration 1) and 4.5 - 0.2 (concentration 2). The gene expression increased in two isolates and decreased in five isolates. The melting point ranged between 83.63 - 84.200C compared with 75.82 - 85.560C for gyrB gene.